(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: Body physique is influenced to a greater extent by climatic, hereditary, nutritional and racial factors. Since in Bangladesh variegated ethnic groups inhabit in different conditions, no single anthropometric formula is suitable. The stature prediction occupies relatively a central position in the anthropometric research. And estimation of stature of an individual from the mutilated or amputated limbs has obvious significance in the personal identification in the events of murders, accidents or natural disasters. The present study was undertaken to measure the stature, as well as some length and breadth of hand and to determine whether there is any correlation between the stature and the hand variables. And to estimate using respective multiplication factors the stature from these variables and to assess the effectiveness of the above estimations by comparing the ‘estimated’ values with the ‘measured’ values. Methods: The study was carried out with a total number of 100 Christian Garo adult females aged between 25 to 45 years. Hand length and breadth along with their stature were measured directly from the subjects by using anthropometric sliding, spreading calipers and measuring tape. The data were then statistically analyzed by computation to find out its normative value. Multiplication factors were estimated for estimating stature and comparison were made between measured and estimated stature using paired "t" test. Result: The mean normal values of the hand measurements (right and left hand length were 16.39 ± 0.72 cm and 16.33 ± 0.67 cm respectively and breadth of right and left hand were 7.22 ± 0.38 cm and 7.18 ± 0.3 cm respectively) and the stature (152.79 ± 5.62 cm) were found. The multiplication factors were estimated for the same hand measurements with the stature. Significant positive correlation was found in case of hand length with the stature. There was positive correlation (r=0.17, p=0.09 and r=0.15, p=0.12) between the stature and breadth of the right and left hand (Figure 3.21) but the result did not reach any statistically significant level. Key words: Anthropology; correlation; multiplication factor; stature DOI: 10.3329/bja.v8i1.6105 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 21-27